DETERMINATION OF STATURE FROM THE LENGTH OF ULNA: A STUDY IN MIZO FEMALES (Journal of Forensic Medicine & Toxicology, 2023)
Estimation of stature from incomplete skeletal and decomposing human remains becomes most important for personal identification from the mutilated or amputated limbs or parts of limbs. The present study was done with an aim to estimate the stature from the length of ulna. Ulna was chosen because compared to other bones of the limb, measurement of ulnar length is easier in living subjects. The present study was conducted in Zoram Medical College, Falkawn, Mizoram and comprised of 66 healthy Mizo females within the age group of 20-50 years. The length of the right and left ulna was measured using a measuring tape and the height with a stadiometer. The regression model was derived to estimate the height of an individual from the ulna. The study showed strong positive correlation between the ulna and height of the individual (pd”0.05).
Keywords: length of ulna; height; linear regression